Application of Child Friendly Schools Through the Hizbul Wathan an Indonesia and Malaysia Elementary Schools: Penerapan Sekolah Ramah Anak Melalui Gerakan Kepanduan Hizbul Wathan pada Sekolah Dasar di Indonesia dan Malaysia - Eni Fariyatul Fahyuni; Imam Fauji; Muhamad Nashiiruddin Addaa'i; Norhapizah, Mohd Burhan; Mahfuzah, Mohamed Zabidi (Halaqa: Islamic Education Journal, 2020)
The child-friendly schools through the Hizbul Wathan movement in SD Muhammadiyah Candi 1 Sidoarjo aims to the leadership character is healthy, knowledgeable and moral. Technique collection data use the method of observation, interviews, and documentation supported by triangulation of sources and strategies. The implementation of Hizbul Wathan movement is divided into 5 stages, including: (a) the planning stage, (b) the organizing stage, (c) the implementation phase, (d) the monitoring and evaluation, and (e) the follow-up. The results that inculcation of leadership character integrated into the values of Al Islam and Kemuhammadiyahan was able to teach the values, rules, norms in every life in society.